2000
DOI: 10.1115/1.1400116
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Pressure- and Temperature-Sensitive Paints to an Advanced Compressor

Abstract: An innovative pressure-measurement technique that employs the tools of molecular spectroscopy has been widely investigated by the aerospace community. Measurements are made via oxygen-sensitive molecules attached to the surface of interest as a coating, or paint. The pressure-sensitive-paint (PSP) technique is now commonly used in stationary wind-tunnel tests; this paper presents the use of this technique in advanced turbomachinery applications. New pressure- and temperature-sensitive paints (P/TSPs) have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 14 publications
0
8
0
3
Order By: Relevance
“…There have been several studies involving the use of PSP for measurement of steady pressures in turbomachinery. Investigations such as those of Liu et al [98], Torgerson et al [99], Bencic [100], Jordan et al [59,60], or Navarra et al [101] have effectively implemented PSP and TSP for measurement of steady pressures in the rotating frame of reference. Very few investigations, however, have attempted to resolve the unsteady pressure fluctuations inherent in turbomachinery.…”
Section: Turbomachinerymentioning
confidence: 99%
“…There have been several studies involving the use of PSP for measurement of steady pressures in turbomachinery. Investigations such as those of Liu et al [98], Torgerson et al [99], Bencic [100], Jordan et al [59,60], or Navarra et al [101] have effectively implemented PSP and TSP for measurement of steady pressures in the rotating frame of reference. Very few investigations, however, have attempted to resolve the unsteady pressure fluctuations inherent in turbomachinery.…”
Section: Turbomachinerymentioning
confidence: 99%
“…To account for model distortions, eight marker dots were applied to the surface with a felt tip pen at known locations. The location of each marker dot was entered into the OMS software and image registration was accounted for using an eight-step quantum pixel energy distribution (QPED) algorithm as described by Navarra et al (2001) with three iterations and an initial box size of 16 × 16 pixels. Due to the paint's thermal and pressure dependence, the PSP was calibrated by a second-order least-squares approximation with known temperatures and pressures.…”
Section: Schlieren Photographymentioning
confidence: 99%
“…Rotor blades are a suitable object to which to apply fast response PSPs. In this paper, we focus on the application of fast-response PSP to compressors [14][15][16][17]. From the PSP measurement point of view, a remarkable characteristic of compressors is that the temperature of the measurement environment exceeds 100 • C. Previous studies have demonstrated that measurements can be made, but it is not clear whether the accuracy is sufficient to evaluate the performance of the compressor.…”
Section: Introductionmentioning
confidence: 99%